2022
DOI: 10.3390/educsci12120884
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Parents and Teachers with Virtual Classrooms during the COVID-19 Restrictions: A Study Focusing on Inclusive Education in Malaysia

Abstract: The COVID-19 pandemic has resulted in emergency remote teaching in many countries. In Malaysia, not all households were prepared for remote teaching. This has caused some groups of students to be left out. Therefore, in this study we aim to investigate the experiences of parents and teachers concerning inclusiveness of the education delivered via virtual classrooms during the pandemic time in Malaysia. Questionnaires were distributed online to gather feedback from parents, teachers and anyone having both roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The affective domain. Previous studies investigating online teaching have revealed that teachers who possessed a higher level of affection were more likely to be aware of the unique challenges faced by students in an online teaching and learning environment [6][7][8]19,[38][39][40]. Some teachers in these studies were willing to learn more so that they could make necessary changes to adapt to the diversity among their students and address inequality by providing, for example, an asynchronous mode of teaching and learning and various digital contents that helped students to understand better, and so forth.…”
Section: Collarations Between Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The affective domain. Previous studies investigating online teaching have revealed that teachers who possessed a higher level of affection were more likely to be aware of the unique challenges faced by students in an online teaching and learning environment [6][7][8]19,[38][39][40]. Some teachers in these studies were willing to learn more so that they could make necessary changes to adapt to the diversity among their students and address inequality by providing, for example, an asynchronous mode of teaching and learning and various digital contents that helped students to understand better, and so forth.…”
Section: Collarations Between Domainsmentioning
confidence: 99%
“…Due to COVID-19 restrictions, traditional face-to-face teaching had to be switched to online teaching. It has been a challenge for many teachers to ensure that all students attending classes on digital platforms receive the same and equal opportunities to learn, as they did before the pandemic, in physical classrooms [6][7][8][9]. On 5 May 2023, the World Health Organization announced that COVID-19 was no longer a public health emergency of international concern [10], and many schools had even returned to traditional face-to-face teaching when restrictions were lifted before this…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the educational inclusion of people with special needs, distance education can become a real opportunity to actively participate in learning along with the rest of the population [20,21]. Such a process, according to the information provided, should be accompanied by educational designs and assistive technologies that balance the inequalities of social and family origins of people with special educational needs, the differences in pedagogical capacities for technology-mediated education, and skills in the use of emerging technologies designed for various types of disability [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…To address the difficulties and resource needs of institutionalizing blended learning, administrators must also enable collaborations with other institutions (Lim & Wang, n.d.). An extensive number of financial resources, technological infrastructure, and pedagogical and technical assistance are needed for the integration of blended learning at a higher education institution (Phua et al, 2022). Administrators can actively look for relationships with other institutions to exchange knowledge, work together to solve problems and obtain funding for blended learning programs (Romero-Hall & Ripine, 2021).…”
Section: Introductıonmentioning
confidence: 99%